Tinjauan Yuridis Etika Berkomentar di Media Sosial Instagram @Pertamina Berdasarkan Pasal 28 Ayat (2) Undang-Undang Nomor 11 tahun 2008 tentang Informasi dan Transaksi Elektronik - Miftia Nur Annisa; Rina Arum Prastyanti; Muhamad Habib (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2025)
This study examines violations of ethical commenting on the Instagram account @Pertamina, in response to a fuel-mixing corruption case that caused state losses of up to one quadrillion rupiah. The research aims to describe forms of unethical comments posted by netizens and analyze them based on Article 28 paragraph (2) of Indonesia’s Electronic Information and Transactions Law (ITE Law). A normative juridical method was used, supported by digital observation, documentation, and note-taking techniques. The results revealed 20 comment samples containing hate speech, insults, threats, and defamation. These comments not only violate digital ethics but also potentially breach Articles 28(2) and 27(3) of the ITE Law. According to Soedikno Mertokusumo's theory of legal objectives, such comments fail to uphold justice, legal certainty, and usefulness, ultimately damaging the digital public space, which should foster healthy and productive communication.